Budowa i przebudowa ratusza w miastach Królestwa Polskiego do końca XVIII wieku - Krasnowolski, Bogusław (Roczniki Dziejów Społecznych i Gospodarczych, 2014)
The construction and reconstruction of town halls in the cities of the Kingdom of Poland until the end of the 18th century (Summary) The article, which also takes into account the issues relating to the medieval town halls in Silesia, Western Pomerania and the Teutonic State, is an attempt at synthesizing the existing research. The following aspects have been analysed: the location of the town hall within the urban complex and the transformation of the forms and symbols of both its architecture and design. Town halls came into existence as a consequence of – although not necessarily immediately – founding towns based on German Law and the establishment of municipal authorities. The relationship between the town halls and urban planning varied. The town hall could be located along the front of the main market square (Wieliczka in Małopolska) or a street – a place functioning as the market square (evolution of the urban context in the town hall in Gdańsk), sometimes (due to the location of the house of the municipal councillor?) outside the market place (originally in Nowy Sącz). Its location along the front of the market square in Early Modern towns could have both an aesthetic and symbolic aspect (Zamość). The evolution of the central-market square block, with the town hall and stalls was very characteristic of medieval towns and infl uenced the Małopolska region (Kraków) and Wielkopolska region (Poznań) from Silesia (Wrocław, Świdnica, Legnica). In Early Modern private towns, from the Renaissance era (Głowów) to the late Baroque (Siedlce), the town hall was often situated in a place which emphasized the axes of the urban layout. The tower was usually an important element in the architecture of the oldest town hall buildings (13th/14th century). It emphasized the town’s autonomy and, similarly to the adjacent hall, was derived from the architecture of feudal castles (Wrocław, Kraków). The tower also emerged as the oldest element of the central-market square block in many Silesian towns, and was modelled on the beffrois (Bruges). The form of a tower came to the Małopolska region in the 14th century (the oldest town hall in Sandomierz) and Ruthenia (Krosno, Kamieniec Podolski). Two-naved halls which alluded to the palatium (Poznań), were particularly frequent in Western Pomerania (Stargard, Pasłęk, Kamień Pomorski, Chojnice, Szczecin). By contrast to the simple, purely functional architectural forms of the oldest town halls, in the lands of the Teutonic knights fi ne details were present as early as in the early 14th century (Chełmno). The richness of the forms and designs of the Pomeranian town halls, with Toruń at the forefront (which Jan Długosz noticed) had an impact on the late Gothic town halls in the Małopolska region (reconstruction of the Kraków town hall, 1454). The transfer of the offi cial functions from the ground floor of the town hall to the Artus Court could also relate to Kraków. Bohemian models played a large role in the shaping of representative architecture, symbolism and the iconographic programme of the late Gothic town halls in Silesia (15th/16th century) – e.g. the relationship between the Ladislaus Room in Hradčany and the Lwówek town hall. In Early Modern times the “bipolarity” of architectural designs in Polish lands, which were inspired by ideas coming both from Italy and the Netherlands is most noticeable on examples in the Małopolska region, notably Kraków (attics surmounting the buildings) and Pomerania, notably Gdańsk, where the designs by masters from the Netherlands were subordinated to erudite, complicated political “treaties”. In the Wielkopolska region the Mannerist style inspired by Northern Italian (Serlian) designs was at the forefront as can be seen in the reconstruction of Poznań’s town hall. In the era of urban decline in the Polish-Lithuanian Commonwealth (2nd half of the 17th/18th century) anachronistic, medieval designs continued to be used (Stary Sącz); private towns were an exception (e.g. Leszno and Buchacz owned by the Leszczyński family), which were able to afford magnificent constructions. The architecture and design of town halls refl ect the ambitions as well as the condition of the bourgeoisie and therefore the phenomena which took various forms in the different historical periods and regions. Future research should put special emphasis on tracing the “migration” of designs and ideas from the magnifi cent urban centres of the West through the main Polish cities to provincial towns.